Comparative effects of two therapeutic complexes on vascular wall activity in patients with arterial hypertension, metabolic syndrome, and recent ocular vessel occlusion - I. N. Medvedev; O. A. Danilenko (Кардиоваскулярная терапия и профилактика)
Aim. To compare the effects of two therapeutic complexes (valsartan or losartan in combination with pioglitazone and non-pharmaceutical intervention) on vascular wall function in patients with arterial hypertension (AH), metabolic syndrome (MS), and recent ocular vessel occlusion. Material and methods. In total, the study included 47 patients (20 men, 27 women) with Stage 1-2 AH, Risk 4 (2008 DAH criteria). Mean age of the participants was 47,9±1,7 years. The age-matched control group included 25 healthy volunteers. Lipid profile, plasma lipid peroxidation, and vascular hemostasis parameters were assessed. To control blood pressure (BP) levels, 24 patients were administered valsartan (160 mg once a day), and 23 received losartan (100 mg once a day). Аll patients received pioglitazone (30 mg once a day) and non-pharmaceutical intervention. Results. The four-month complex therapy with valsartan normalised vascular wall function in AH patients with MS and ocular vessel occlusion. The complex therapy with losartan improved, but not normalized vascular wall function. The subsequent poor compliance with non-pharmaceutical therapy, even with continuing pharmaceutical treatment, reduced the beneficial effect of the complex therapy, which could be explained by persisting thrombosis risk in this clinical group. Conclusion. The complex intervention was more effective in combination with valsartan, and less effective in combination with losartan, in improving vascular hemostasis.